The Discovery of Novel Circulating Cancer‐Related Cells in Circulation Poses New Challenges to Microfluidic Devices for Enrichment and Detection. Issue 7 (20th May 2022) - Wu, Man; Huang, Yuhang; Zhou, Yang; Zhao, Hui; Lan, Yuwei; Yu, Zhibin; Jia, Chunping; Cong, Hui; Zhao, Jianlong
Abstract: Circulating tumor cells (CTCs) enumeration has been widely used as a surrogate predictive marker for early diagnoses, the evaluation of chemotherapy efficacy, and cancer prognosis. Microfluidic technologies for CTCs enrichment and detection have been developed and commercialized as automation platforms. Currently, in addition to CTCs, some new types of circulating cancer‐related cells (e.g., CCSCs, CTECs, CAMLs, and heterotypic CTC clusters) in circulation are also reported to be correlated to cancer diagnosis, metastasis, or prognosis. And they widely differ from the conventional CTCs in positive markers, cellular morphology, or size, which presents a new technological challenge to microfluidic devices that use affinity‐based capture methods or size‐based filtration methods for CTCs detection. This review focuses on the biological and physical properties as well as clinical significance of the novel circulating cancer‐related cells, and discusses the challenges of their discovery to microfluidic chip for enrichment. Finally, the current challenges of CTCs detection in clinical application and future opportunities are also discussed. Abstract : In addition to circulating tumor cells (CTCs), some new types of circulating cancer‐related cells in circulation are also reported to be correlated to cancer diagnosis, metastasis, or prognosis. And they widely differ from the conventional CTCs in positive markers, cellular morphology, or size, which presents new technological challenges to microfluidic devices for CTCs detection. This review provides promising solutions for these challenges.